Agile foundation : principles, practices and frameworks - Measey, Peter (BCS, 2015)
"Agile practices transform the way organisations carry out business and respond to change. But to realise success, an agile mindset needs to be adopted throughout an organisation, not just within the IT team. This book is aimed at those working in an agile environment or wanting to understand agile practices. Giving a comprehensive introduction to agile principles and methodologies, it will enable readers to apply core values and principles of agile methods in their organisation. This is the official textbook for the BCS Agile Foundation certificate."-- Unedited summary from book
Keywords: Agile software development.; Project management.; elektronické knihy; electronic books